Epidemiologia e investigação de mecanismos de resistência aos carbapenêmicos e polimixinas em bacilos gram-negativos multirresistentes - Lorenzoni, Vinicius Victor (2018)
Bacterial resistance is a global public health problem and leads to relapsing nosocomial infections, high morbidity and mortality rates and high financial impact. Carbapenems and polymyxins are extensively antimicrobials agents used for treatment of multidrug-resistant Gram-negative microorganisms. Several mechanisms of resistance to these drugs have been reported, such as the production of β-lactamases (e.g. Klebsiella pneumoniae carbapenemase, metallo-β-lactamases and oxacillinases), modifications in outer membrane (e.g. changes in PmrAB/PhoPQ component systems and in lipid A) and efflux systems, limiting therapeutic options. The aim of this study was to determine the epidemiological profile of 3069 multidrug-resistant Gram-negative bacilli clinical isolates from the Hospital Universitário de Santa Maria between the years 2015 and 2017 and to detect resistance to carbapenems and polymyxins by phenotypic (disc diffusion with enzymatic inhibitors, Carba-NP, Blue-Carba and Polymyxin NP) and molecular methods (Polymerase Chain Reaction and sequencing). Presence of KPC in 80% of carbapenem-resistant Enterobacteriaceae was verified, as well as the presence of blaKPC gene by conventional PCR. Disk diffusion with enzymatic inhibitors, Carba-NP and Blue-Carba phenotypic tests showed 100% sensitivity and specificity to detect the presence of carbapenemases. Polymyxin NP test demonstrated 100% sensitivity and specificity to detect resistance to colistin in 340 Gram-negative bacilli (Enterobacteriaceae, Acinetobacter baumannii and Pseudomonas aeruginosa) with reduced sensitivity to polymyxins. Among them, the plasmid-mediated mcr-1 gene was present in one colistin-resistant Escherichia coli isolate (MIC 64 μg/mL) recovered from blood culture, detected by conventional PCR and confirmed by Sanger sequencing method. The ability to transmit the gene was investigated by bacterial conjugation with azide-resistant E. coli J53 and a colistin-resistant transconjugant (MIC 4 μg/mL) and carrier of the mcr-1 gene were obtained. A temporal analysis of antimicrobial resistance in 2659 K. pneumoniae isolates between the years 2015 and 2017 showed and increase resistance to colistin (532.8%), amikacin (142.8%), meropenem (85.1%), imipenem (79.5%), tigecycline (77.7%), ciprofloxacin (66.7%), gentamicin (51.9%) and ertapenem (36.1%). Therefore, the main genes detected in the study were blaKPC and mcr-1, and the phenotypic tests presented excellent performance, making possible the use in the laboratory routine. In view of the foregoing, it’s fundamental to reinforce the implantation of stricter infection control measures, and adequate therapeutic planning, as this phenotype is accelerated by the dissemination of high-risck clones and resistance genes mediated by mobile genetic elements, such as plasmids, as well as indiscriminate use of antimicrobials agents.